Exploring the Value Addition Strategies to Access Standards of Products of Micro, Small and Medium Entrepreneurs in Jaffna District - Sathana, V. (Macrothink Institute, 2018)
After the local war, micro, small and medium enterprises (MSMEs) have been facing huge problems in Jaffna District and they have poor quality of product and services. The purpose of this paper is to explore the meaningful value addition strategies to access standards for products of micro, small and medium entrepreneurs (MSMEs) for establishing a competitive advantage. Coconut is vital sector of SMEs and also one of the major resources in Jaffna district. This sector has the greatest prospects for growth and development. Value addition for coconut based productions leads to more quality and creates adequate demand for the products. Thus researcher scoped coconut sector among the MSMEs. The research is qualitative in nature with exploratory narrative research. Under purposive sampling technique, the owners or managers of enterprises and stake holders of MSMEs were interviewed by using unstructured questions to explore the value addition. The author proposed two momentous models; they are model of values addition strategies to access standards as a tool for competitive advantage and collaborative institutional model to access standards with the participation of government and non-government organizations. The findings are; first model induces MSMEs to access standards and second model explains the means to achieve the standard. Especially this research expresses the essential of sincere collaborative work of institutions towards the quality productions and development of MSMEs. Further this research points out that the notion of value addition practices has been evolved and is increasingly understood consideration for economic development of Sri Lanka.
Keywords: Value addition; Micro, small and medium enterprises; Coconut based productions; Quality standards